Robust filtered Smith predictors for networked control systems with packet-based data transmission. (March 2022) - Steinberger, Martin; Horn, Martin
Abstract: Filtered Smith predictors are well established for controlling linear plants with constant time delays. Apart from this classical application scenario, they are also employed within networked control loops, where the measurements are sent in separate packets over transmission channels that are subject to time-varying delays. Consequently, classical tools for the stability analysis, e.g., for time delay systems, have to be extended to facilitate an explicit consideration of network-induced effects such as packet skipping and disordering of sent packets. The present paper illustrates that the time-varying delays and, particularly important, the packetized character of the transmissions have to be explicitly taken into account for the stability analysis. Three network protocols, which use different packet selection and hold mechanisms, are considered to state criteria for the robust stability of the networked feedback loops with filtered Smith predictors. They are based on the small gain theorem and allow a computationally inexpensive way to check stability for the case with uncertain plant models and bounded time-varying packet delays in the communication channels. Highlights: Filtered Smith predictor for packet-based networked systems. Communication network with bounded and time-varying packet delays. Three different network protocols (different packet skipping and hold mechanisms). Easy-to-use stability analysis for uncertain plants and time-varying packet delays.